Clinical significance of the tumor microenvironment on immune tolerance in gastric cancer - He, Xiangyang; Guan, Xin-Yuan; Li, Yan (Frontiers in Immunology, 2025)
In the realm of oncology, the tumor microenvironment (TME)—comprising extracellular matrix components, immune cells, fibroblasts, and endothelial cells—plays a pivotal role in tumorigenesis, progression, and response to therapeutic interventions. Initially, the TME exhibits tumor-suppressive properties that can inhibit malignant transformation. However, as the tumor progresses, various factors induce immune tolerance, resulting in TME behaving in a state that promotes tumor growth and metastasis in later stages. This state of immunosuppression is crucial as it enables TME to change from a role of killing tumor cells to a role of promoting tumor progression. Gastric cancer is a common malignant tumor of the gastrointestinal tract with an alarmingly high mortality rate. While chemotherapy has historically been the cornerstone of treatment, its efficacy in prolonging survival remains limited. The emergence of immunotherapy has opened new therapeutic pathways, yet the challenge of immune tolerance driven by the gastric cancer microenvironment complicates these efforts. This review aims to elucidate the intricate role of the TME in mediating immune tolerance in gastric cancer and to spotlight innovative strategies and clinical trials designed to enhance the efficacy of immunotherapeutic approaches. By providing a comprehensive theoretical framework, this review seeks to advance the understanding and application of immunotherapy in the treatment of gastric cancer, ultimately contributing to improved patient outcomes.